Near‐Infrared Light Driven Photopolymerization Based On Photon Upconversion. Issue 11 (12th March 2019) - Chen, Zhijun; Wang, Xue; Li, Shujun; Liu, Shouxin; Miao, Hui; Wu, Si
Abstract: Near‐infrared (NIR) light is an ideal source for initiating polymerization because of the lower energy of NIR photons and considering that NIR light usually has deeper penetration depth in materials than UV light. Recently, lanthanide‐doped upconverting nanoparticles (UCNPs) were used for NIR photopolymerization. UCNPs convert NIR light to UV or visible light, which can subsequently be absorbed by photosensitizers or photoinitiators. Subsequently, the excited photosensitizers/photoinitiators trigger polymerization. This process is referred to UCNP‐assisted photopolymerization. Herein, recent progress in UCNP‐assisted photopolymerization is introduced, applications of materials prepared via this type of reaction are highlighted, and the associated challenges are discussed. Abstract : On your marks, get set, go ! The development of upconversion nanoparticle (UCNP) assisted photopolymerization, applications and perspectives are reviewed. The combination of upconverting materials and various photosensitizers/photoinitiators were summarized and various applications in biomedicine, deep curing and 3D printing were discussed.